2009
DOI: 10.1007/s10549-009-0415-0
|View full text |Cite
|
Sign up to set email alerts
|

Green tea consumption and breast cancer risk or recurrence: a meta-analysis

Abstract: Green tea is a commonly consumed beverage in Asia and has been suggested to have anti-inflammatory and possible anti-carcinogenic properties in laboratory studies. We sought to examine the association between green tea consumption and risk of breast cancer incidence or recurrence, using all available epidemiologic evidence to date. We conducted a systematic search of five databases and performed a meta-analysis of studies of breast cancer risk and recurrence published between 1998 and 2009, encompassing 5,617 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 29 publications
2
82
0
3
Order By: Relevance
“…An inverse association between green tea and breast cancer risk was reported from case-control data, while no association was observed from cohort data [64]. The nested case-control study reported no association [65], so even if it had been included as a cohort study in the pooled analyses, the overall finding would have remained the same.…”
Section: Cancermentioning
confidence: 92%
See 1 more Smart Citation
“…An inverse association between green tea and breast cancer risk was reported from case-control data, while no association was observed from cohort data [64]. The nested case-control study reported no association [65], so even if it had been included as a cohort study in the pooled analyses, the overall finding would have remained the same.…”
Section: Cancermentioning
confidence: 92%
“…The most recent meta-analysis included 7 (2 cohort, 1 nested case-control and 4 casecontrol) epidemiological studies of green tea and breast cancer that were published as of December 2008 [64]. An inverse association between green tea and breast cancer risk was reported from case-control data, while no association was observed from cohort data [64].…”
Section: Cancermentioning
confidence: 99%
“…Four were population-based studies conducted among Asians in USA and Europe Seely et al, 2005;Ogunleye et al, 2010), one in Shanghai, China (Shrubsole et al, 2009), and one hospital-based study was in Zhejiang Province, China (Zhang et al, 2007). All these six studies showed significant breast cancer risk reduction among the population with regular green tea drinking.…”
Section: Prevention Of Cancermentioning
confidence: 99%
“…Because catechin absorption from the intestines to the bloodstream is relatively low [4], a high dose of about10 cups/d in addition to along duration of green tea consumption maybe necessary to achieve an inverse association between green tea consumption and cancer incidence. Although inconsistent results have been observed in a case-controlled study and a prospective study, Li et al showed that there was a statistically significant 19% reduction of breast cancer incidence among woman with high green tea intake in the most recent meta-analysis of two cohort studies and five casecontrolled studies [34][35][36][37][38][39][40][41].…”
Section: Prostate Cancermentioning
confidence: 99%